Fearless : how an underdog becomes a champion - Pederson, Doug; Pompei, Dan (Hachette Books, 2018)
"How does an underdog become a champion? One of the most innovative, gutsy, and dynamic head coaches in the NFL reveals the strategies behind building the Eagles team that shocked the world by winning the Super Bowl." -- Amazon.com